Role of neutrophil-lymphocyte ratio in determining the outcomes of preterm premature rupture of membranes - Lakshmi, M. P. A. Sai; Sravani, V. Lakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Premature Rupture of Membranes (PROM) is a significant obstetric problem. Evaluation of neutorphil-lymphocyte ratio (NLR) is expected to throw light on the potential scope of early prediction of PPROM. With this background, the present study was carried out to compare the NLR among preterm PROM and healthy controls to evaluate the predictive role of NLR and platelet-lymphocyte ratio (PLR). Methods: This case control study was carried out among 101 pregnant women 44 pregnant women diagnosed with Preterm PROM and 55 term gestation matched healthy controls. Laboratory parameters (including complete blood count were measured. PLR was calculated as the number of platelets divided by the lymphocyte count, and NLR was calculated by dividing the neutrophil Count by the lymphocyte count, both of which were obtained from the same blood samples. Results: All the inflammatory markers including total count, neutrophil count, NLR and PLR ratios were elevated among PPROM group compared to the controls. The observed differences in the mean levels of these parameters were statistically significant (p<0.05). Conclusions: It may be considered that monitoring of NLR during second and early third trimesters as a routine practice among high risk mothers can significantly help in early prediction of PPROM and help in minimizing adverse maternal and neonatal outcomes.